A auto(trans)formação permanente e a pedagogia de educação popular: entrelaçamentos possíveis entre a práxis educativa escolar e a realidade dos estudantes - Signor, Patrícia (2016)
This Master's Thesis is part of the Training Line of Research, Knowledge and Professional Development of the Graduate Program in Education of the Federal University of Santa Maria / RS. The research aimed to study and understand the continuing self(trans)formation of teachers and students by the web of school educational practice with the popular pedagogy possible in the context. It was necessary to infer the continuing self(trans)formation as an articulator of the context of students and teachers daily; understand the self(trans)formation experience of Circles, as a contribution to the education of the teachers in the context of a public school of Basic Education to build a more meaningful and humane education for their subjects and to investigate how continuing self(trans)formation, intertwined with popular pedagogy, can contribute to educational practice with a bias of significant changes to students. To conduct the survey, the concepts of continuing education were intertwined (Freire, 2011a), teacher training (IMBERNÓN, 2009), held along the career path and life experiences, especially when it occurs in times of training conducted with focus on everyday school. Along with the continuing self(trans)formation education (HENZ, 2014; 2015), the work brings the contributions of Freire s popular pedagogy (2014; 2013; 2011) as an opportunity to public school and a more meaningful education to learners and educators/teachers, so it is a learning space and experience with the seriousness of the profession and the joy of learning constantly. The chosen methodological approach was qualitative, supported by Ghedin & Franco (2011); André (2001); Duarte (2002); Michel (2009), based on Investigative-training Dialogic Circles (HENZ, 2014), (FREITAS, 2015), (HENZ; FREITAS, 2015) that emphasize opportunities for dialogue and self(trans)formation teacher training with emphasis and proximity in the daily of the students involved with the community and the reality of the subject. The methodology is characterized by a case study (YIN, 2005) since it favors a particular context and investigates intensively the particularities with characteristics of research participant (BRANDÃO, 2001), as the researcher has immersion and participation in the context of research and the work issues of needs perceived by the group watching and analyzed daily. The research took place through five Dialogic Circles Investigative-training and another devolutive Circle and research validation with the collective of teachers of the State School of Basic Education Antônio João Zandoná of Barra Funda (RS), which, since 2003, works with a methodology of generating themes from the perspective of popular pedagogy of Paulo Freire (2013). The research caused an intertwining between the continuing self(trans)formation and popular education pedagogy to build links between the school educational practice and the context of students with a view to the possibility of renewal and enhancement of public school as a place to learn, grow, politicized, humanize and be happy. The hermeneutic analysis (GADAMER, 1998; FLICKINGER, 2014, KRONBAUER, 2014) noted that the dialogue as a research methodology has much to contribute to the self(trans)formation times of educators, co-authors of the research, from everyday issues and disquieting that emerged from the circles, leading them to the realization that the self(trans)formation may contribute to novel-viable in building a more problematical, dialogue and human education.